Virtual Chemistry Laboratory in Blended Online Learning Mode: The Influence on Students’ Motivation and Achievement - Ikhsan, Jaslin; Fitriyana, Nur; Arif, Zulham (Pedagogika, 2023)
This study aimed to seek the influence of ViChem-Lab in blended online learning mode towards students’ motivation and achievement in chemistry. A quasi-experiment with prie and post-test non-equivalent control group design was implemented. The findings illustrate that the use of ViChem-Lab in blended online learning gives the strongest influence on self-efficacy, curiosity, attention, and satisfaction, respectively, as part of students’ motivation. It implied the rise of students’ achievement.